2016
DOI: 10.1371/journal.pone.0159591
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Sex-Biased MicroRNAs in Bactrocera dorsalis (Hendel)

Abstract: MicroRNAs (miRNAs) are a class of endogenous small non-coding RNAs that regulate various biological processes including sexual dimorphism. The oriental fruit fly Bactrocera dorsalis is one of the most destructive agricultural insect pests in many Asian countries. However, no miRNAs have been identified from the separate sex and gonads to elucidate sex gonad differentiation in B. dorsalis. In this study, we constructed four small RNA libraries from whole body of females, males (except ovaries and testes) and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
1
16
1
Order By: Relevance
“…melanogaster , where expression was preferentially associated with the reproductive functions [ 78 ]. More recent work that compared miRNA expression between mature male and female reproductive organs in Bactrocera dorsalis demonstrated that sex-biased miRNAs are likely involved in sexual differentiation [ 79 ]. Furthermore, the expression of miRNAs varied across developmental stages of Xenopus laevis [ 80 ] and across different human tissues [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…melanogaster , where expression was preferentially associated with the reproductive functions [ 78 ]. More recent work that compared miRNA expression between mature male and female reproductive organs in Bactrocera dorsalis demonstrated that sex-biased miRNAs are likely involved in sexual differentiation [ 79 ]. Furthermore, the expression of miRNAs varied across developmental stages of Xenopus laevis [ 80 ] and across different human tissues [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a dipteran insect, B. dorsalis is a typical holometabolous insect that undergoes larval–pupal metamorphosis. Additionally, several studies have shown that miRNAs are involved in B. dorsalis development and reproduction (Huang et al, 2014; Peng et al, 2016, 2017). Considering the diverse roles of miRNAs, some miRNAs in the regulation of gene expression during metamorphosis probably exist in B. dorsalis .…”
Section: Introductionmentioning
confidence: 99%
“…Various insects such as Drosophila melanogaster [ 7 ], Bombyx mori [ 8 ], Blattella germanica [ 9 ], Apis mellifera [ 10 ] and Aedes aegypti [ 11 ] have also been reported to encode miRNAs that play important roles in development, adaptation and host-virus interactions. The analysis of small RNA libraries generated from various developmental stages in different species enables an in-depth study of miRNA in physiological processes [ 12 ]. In insects, including D .…”
Section: Introductionmentioning
confidence: 99%